Equine flexor tendon imaging part 2: Current status and future directions in advanced diagnostic imaging, with focus on the deep digital flexor tendon. (December 2021) - Ehrle, Anna; Lilge, Svenja; Clegg, Peter D.; Maddox, Thomas W.
Highlights: Magic angle and contrast media have potential to enhance flexor tendon MRI. Computed tomography is increasingly used in equine orthopaedic soft tissue imaging. Positron emission tomography and ultra-high field MRI provide future prospects in tendon imaging. Abstract: Flexor tendon injuries are a common cause of lameness and early retirement in equine athletes. While ultrasonography is most frequently utilised, advanced diagnostic imaging modalities are becoming more widely available for detection and monitoring of flexor tendon lesions. Part two of this literature review details current experience with low- and high-field magnetic resonance imaging (MRI) and computed tomography (CT) for the diagnosis of equine flexor tendinopathy with a focus on the deep digital flexor tendon. Implications of the 'magic angle' artefact as well as injection techniques and the use of contrast media are discussed. Future developments in tendon imaging aim to gain enhanced structural information about the tendon architecture with the prospect to prevent injury. Techniques as described for the assessment of the human Achilles tendon including ultra-high field MRI and positron emission tomography are highlighted.